Environment-friendly epoxidation of limonene using tungsten-based polyoxometalate catalyst - López Fernández, Ana María; Rehman, Abdul; Mukhtar Gunam Resul, Mohamad Faiz; Saleem, Faisal; Ahmad, Sajjad; Eze, Valentine C.; Harvey, Adam P. (Elsevier, 2023)
Terpene epoxides play a vital role as chemical intermediates in industries such as flavourings, fragrances, paints, and polymers manufacturing. However, current methods for limonene epoxidation suffer from low selectivity and environmental concerns. To address these limitations, we aimed to develop a highly selective and environmentally benign process for limonene epoxidation. Our approach involved employing hydrogen peroxide (H2O2) as an oxidant in the presence of tungsten-based polyoxometalates as catalysts. A novel catalyst was synthesized using sodium tungstate dihydrate (Na2WO4‹…2H2O), phosphoric acid (H3PO4), sulfuric acid (H2SO4), and sodium sulfate (Na2SO4) as an inorganic salt. We investigated the influence of various process variables, including the limonene:H2O2 molar ratio, reaction time, temperature, and solvent type, to optimize the epoxidation process. Through systematic screening, we achieved remarkable results, attaining 96 limonene conversion, 80 selectivity to limonene-1,2-epoxide, and 19 selectivity to limonene bis-epoxide within a short reaction time of 15 min. Notably, this high performance was accomplished by introducing H2O2 in a single step. To mitigate the hydrolysis of the epoxide, we employed sodium sulphate (Na2SO4) to saturate the reaction mixture. Furthermore, we proposed a comprehensive mechanism for the limonene epoxidation process using tungsten-based polyoxometalates as catalysts. Our kinetic study revealed a first-order reaction with respect to both limonene and the catalyst. Importantly, the decomposition of H2O2 was negligible under the investigated operating conditions, confirming the stability and efficiency of our approach. Our findings present eco-friendly, scalable, and catalytic epoxidation methods as valuable synthetic tools for converting inexpensive bio-renewable terpene feedstocks into essential chemical building blocks. The implications of our work extend to the synthesis of useful chemical products in a biorefinery setting, promoting a more sustainable and efficient utilization of terpenes.